Pengaruh Komunikasi Atasan Bawahan Dan Motivasi Terhadap Kinerja Karyawan Di Ramai Departement Store And Supermarket Yogyakarta - Nerys Lourensius; Thomas Aquinas Radito (Jurnal Solusi, 2018)
This research was carried out in the Ramai Department Store and Supermarket of Yogyakarta. This study aims to examine (1) whether the communication variables of subordinate superiors influence the performance of employees in the Ramai Yogyakarta Dept. Store and Supermarket, (2) Is the motivation variable influencing employee performance in Ramai Yogyakarta’s Dept. Store and Supermarket. The results of testing validity and reliability for the questionnaire showed that 30 questions used were valid and reliable as estimators.Y = 15,243 + 0,263X1+ 0,344X2 +e. Based on the results of regression test, the subordinate supervisor’s communication variable variable (X1) and motivation (X2) has a significant impact on the employee’s performance (Y). While the coefficient of determination is equal to 0.256, meaning that the subordinate supervisor’s communication variable (X1) and motivation (X2) can only affect the employee’s performance by the remaining 25.6%, which is 74.4% influenced by other factors not examined.